2002
DOI: 10.1002/jat.872
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary responses and recovery following single and repeated inhalation exposure of rats to polymeric methylene diphenyl diisocyanate aerosols

Abstract: Acute and repeated inhalation exposures (for 28 days) to polymeric methylene diphenyl diisocyanate (PMDI) were performed in rats. Investigations were made at the end of exposures and after 3, 10 and 30 days of recovery following single acute exposures and after 30 days of recovery following 28 days of exposure. Acute exposures to 10, 30 or 100 mg m(-3) PMDI produced clinical signs in all animals that were consistent with exposure to irritant aerosols. An exposure concentration-related body weight loss and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Inhalation of acid aerosols in laboratory animal studies causes genotoxic damage in cells (Soskolne et al, 1984;Swenberg and Beauchamp, 1997). Kilgour et al (2002) showed cell proliferation of the respiratory tract in rats due to exposure to sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of acid aerosols in laboratory animal studies causes genotoxic damage in cells (Soskolne et al, 1984;Swenberg and Beauchamp, 1997). Kilgour et al (2002) showed cell proliferation of the respiratory tract in rats due to exposure to sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes made up of completely reacted MDI and precipitated surfactant are phagocytized by alveolar macrophages or eliminated via mucociliary clearance from the site of deposition (Pauluhn 2000. The initial event is accompanied by alveolar protein exudation; increased concentrations of total protein serve as a measurement of acute alveolar irritation (Kilgour et al 2002;Pauluhn 2000;. The available findings thus support the hypothesis that lung tumours are caused by chronic regenerative cell proliferation and not by genotoxic initiation and promotion.…”
Section: Mode Of Action In Lung Tumour Formationmentioning
confidence: 53%
“…Cell proliferation data and changes in the BAL seem to correspond (Kilgour et al 2002;. In the case of PMDI, a significant increase in proteins in the BAL of rats was observed immediately after exposure even after single 6-hour exposures to the lowest concentration used of 0.7 mg/m 3 .…”
Section: A)mentioning
confidence: 70%
See 2 more Smart Citations